Le citoyen et la mairie : les collectifs d’habitants dans la construction de l’accueil des exilé·e·s à Paris - Louise Hombert (Association Internationale des Sociologues de Langue Française, 2021)
The "citizens' collectives", which appeared in the wake of the first Parisian camps from 2015 onward, are recent actors in the migrants' reception field. Like more traditional associations or the public institutions social services, these organizations carry out forms of reception and hospitality on a local scale and thus become part of a network of more or less long-standing actors. The aim here is to examine the extent to which these collectives constitute a specific form of organization within this field, and how their appearance influences the conditions of exchange between the reception actors involved in Paris, particularly in terms of local public action structuration.